Chromium accumulation, microorganism population and enzyme activities in soils around chromium-containing slag heap of steel alloy factory - 黄顺红 彭兵 杨志辉 柴立元 周理程 (Transactions of Nonferrous Metals Society of China, 2009)
The environmental risk of chromium pollution is pronounced in soils adjacent to chromate industry. It is important to investigate the functioning of soil microorganisms in ecosystems exposed to long-term contamination by chromium. 45 soil samples obtained from different places of the slag heap in a steel alloy factory were analyzed for chromium contamination level and its effect on soil microorganisms and enzyme activities. The results show that the average concentrations of total Cr in the soil under the slag heap, adjacent to the slag heap and outside the factory exceed the threshold of Secondary Environmental Quality Standard for Soil in China by 354%, 540% and 184%, respectively, and are 15, 21 and 9 times higher than the local background value, respectively. Elevated chromium loadings result in changes in the activity of the soil microbe, as indicated by the negative correlations between soil microbial population and chromium contents. Dehydrogenase activity is greatly depressed by chromium in the soil. The results imply that dehydrogenase activity can be used as an indicator for the chromium pollution level in the area of the steel alloy factory.